MEDIA KUBINO BERBASIS PJBL ADALAH TRATEGI PEMECAHAN MASALAH PEMBELAJARAN PADA DIMENSI 3 DIKELAS XII SMK NEGRI 1 MAGELANG - RUSNI MOHAMAD (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2022)
KUBINOV is a media / teaching aid that can help teachers make it easier to convey / explain material to students, especially in KD 4.1: determining the distance in the wake, namely the distance from the point to the plane is difficult for students to understand, because in this material students must be able to think at a high level, which means students can analyze problems, reason, draw, determine the projection of points on the plane, determine the auxiliary plane to find the distance of the point to the plane. This makes it difficult for students in the material to determine the distance in the wake. The difficulty experienced is designing the teaching aids according to the problem, after being designed and then making them, which requires no small amount of funds. However, the author still makes props for the sake of children so that it is easy to understand the material to determine the distance in the 3rd dimension, so the author makes 8 cubes that are innovated according to the shape of the problem called KUBINOV (cubes that are innovated according to the shape of the question). KUBINOV media can help students more easily understand the concepts of the material being taught and can improve students' reasoning. It also raises student motivation in learning, students are more enthusiastic so that student learning outcomes reach an average of 87 towards mathematics, especially determining the distance in the 3rd dimension compared to before using KUBINOV media the average value of students is only 45. KUBINOV is used in the learning process since 2018 and until now also used by friends in the learning process. ABSTRAKKUBINOV adalah media/alat peraga yang dapat membantu guru memudahkan menyampaikan/menjelaskan materi kepada siswa khususnya pada KD 4.1: menentukan jarak pada bangun ruang yaitu jarak titik kebidang sulit dipahami oleh siswa, dikarenakan pada materi ini siswa harus bisa berpikir tingkat tinggi,yang artinya siswa dapat menganalisis soal, menalarnya, menggambar, menentukan proyeksi titik pada bidang, menentukan bidang bantu untuk mencari jarak titik ke bidang. Hal ini yang membuat siswa sulit pada materi menentukan jarak pada bangun ruang. Kesulitan yang dialami adalah merancang alat peraga sesuai soal, setelah dirancang kemudian pembuatannya yang memerlukan dana tidak sedikit. Walaupun demikian penulis tetap membuat alat peraga demi anak-anak agar mudah paham terhadap materi menentukan jarak pada dimensi 3, sehingga penulis membuat 8 kubus yang di inovasi sesuai dengan bentuk soal yang dinamakan KUBINOV ( kubus yang di inovasi sesuai bentuk soal).  Media KUBINOV dapat membantu siswa lebih mudah memahami konsep materi yang diajarkan dan dapat meningkatkan penalaran siswa. Juga membangkitkan motivasi siswa dalam belajar, siswa lebih semangat sehingga hasil belajar siswa mencapai rata-rata 87 terhadap matematika khususnya menentukan jarak pada dimensi 3 dibandingkan sebelum menggunakan media KUBINOV nilai rata-rata siswa hanya 45. KUBINOV digunakan pada proses pembelajaran sejak tahun 2018 dan sampai sekarang juga digunakan teman-teman pada proses pembelajaran.